Breed and Sex Effect on Meat Quality of Chicken - Chen, G.H.; Cheng, J.H.; Shuiep, E.S.; Bao, W.B.; Musa, H.H. (International Journal of Poultry Science, 2006)
Total of 120 chickens from Anka and Rugao breed includes (60 individual per breed and 30 individual per sex) were taken as a representative sample and were slaughtered at Jiangsu Poultry Institute, China, and then the carcasses were dissected manually. Water holding capacity, color density, pH and tenderness were estimated from breast muscle. Breeds were found differed significantly (P< 0.05) in color density, pH and tenderness. Regarding to water holding capacity no significant (P>0.05) different were noted between breeds. Tenderness, the values for shear force were significantly (P>0.01) higher in males than females in two chicken breeds. In addition color density, pH and water holding capacity were non significantly difference (P>0.05). In Anka chicken breed color density was positive correlated with pH, tenderness and water holding capacity, and similarly pH was positively related with tenderness. While in Rugao all meat quality traits shows negative correlation with each others, specially tenderness was observed positive correlation with color density.